ArtinM Binding Effinities and Kinetic Interaction with Leukemia Cells: A Quartz Crystal Microbalance Bioelectroanalysis on the Cytotoxic Effect. Issue 6 (8th March 2017) - Pesquero, Naira C.; Carvalho, Fernanda C.; Faria, Ronaldo C.; Roque‐Barreira, Maria‐Cristina; Bueno, Paulo R.
Abstract: ArtinM, a D‐mannose‐binding lectin from Artocarpus heterophyllus (jackfruit), interacts with N‐glycosylated receptors on the surface of several cells of hematopoietic origin, triggering cell migration, degranulation, and cytokine release. Because malignant transformation is often associated with altered expression of cell surface glycans, we evaluated the interaction of ArtinM with human myelocytic leukemia cells by Quartz Cristal Microbalance (QCM) and cross compared this investigation with cellular responses (cytotoxicity) to lectin binding by the colorimetric assay MTT, which is a standard method in biology. QCM analysis was able to provide additional information (not possible to be obtained by MTT) that impact on the knowledge of medical biology related to leukemic cells. For instance, it was shown that association rate constant of ArtinM and cellular membranes (obtained from QCM) of leukemia cell varies across the myeloid leukemia cell lines, decreasing as cytotoxic effect increases. Meanwhile no differences were observed for dissociation rate constants so that the equilibrium binding affinity constant was observed to be a direct function of the association rate event. It was supposed that ArtinM cytotoxicity is affected by the association time with glycans on the cellular membranes of leukemia cells in a way that the higher it is the association time (the lower was the association rate constant) the higher is the ArtinM cytotoxicity over the leukemia cell lines. Abstract :